PENGARUH KINERJA PEGAWAI TERHADAP PENINGKATAN PELAYANAN MASYARAKAT DI LINGKUNGAN DINAS TATA RUANG KABUPATEN KUTAI TIMUR - Swarni Marwan (ADMINISTRASI PUBLIK, 2017)
This study is intended to determine the effect on the improvement of the performance of public services in the district spatial East Kutai, therefore the researchers to formulate hypotheses